Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00268-014-2647-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Morphologic Criteria and α‐Fetoprotein in Selection of Patients With Hepatocellular Carcinoma for Liver Transplantation Minimizes the Problem of Posttransplant Tumor Recurrence

Abstract: BackgroundSerum α-fetoprotein concentration (AFP) might be a useful addition to morphologic criteria for selecting patients with hepatocellular carcinoma (HCC) for liver transplantation (LT). The aim of this study was to evaluate the role of AFP in selecting HCC patients at minimal risk of posttransplant tumor recurrence in the setting of existing criteria.MethodsThis retrospective cohort study was based on 121 HCC patients after LT performed at a single institution. AFP was evaluated as a predictor of posttra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…However, it seems difficult to use the cut-off value of 400 ng/mL to directly exclude patients from a waiting list, because this value has been mostly studied as part of algorithms that include tumor volume, tumor size, the MC, and/or the UCSFcriteria. Moreover, many other cutoff values have been suggested, such as 100 ng/mL [47,57,67] and 200 ng/ mL [10,68] . The level of evidence to define an optimal value is very weak and thus calls for further studies.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
“…However, it seems difficult to use the cut-off value of 400 ng/mL to directly exclude patients from a waiting list, because this value has been mostly studied as part of algorithms that include tumor volume, tumor size, the MC, and/or the UCSFcriteria. Moreover, many other cutoff values have been suggested, such as 100 ng/mL [47,57,67] and 200 ng/ mL [10,68] . The level of evidence to define an optimal value is very weak and thus calls for further studies.…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
“…Another Polish study including 121 HCC patients confirmed the validity of 100 ng/mL as cut-off value in predicting the risk of post-LT recurrence in patients meeting San Francisco criteria or up-to-seven criteria [13] . An Egyptian study identified AFP value > 200 ng/mL as a predictive tool for HCC recurrence in 170 living donor LT (LDLT) [14] .…”
Section: Recurrence: Role Of Static Valuesmentioning
confidence: 90%
“…The San Francisco transplant center underlined the recent implementation in their inclusion policy for LT to include patients with AFP levels > 1000 ng/mL only if LRT enabled to decrease this level beneath 500 ng/mL [21] . A Canadian study including 48 patients showed by 1901 July 28, 2015|Volume 7|Issue 15| WJH|www.wjgnet.com McHugh et al [12] 2010 101 United States 100 Grąt et al [13] 2014 121 Poland 100 Abdel-Wahab et al [14] 2013 170 (LDLT) Egypt 200 Lai et al [15] 2011 153 Italy 210 Harimoto et al [16] 2013 167 (LDLT) Japan 300 Merani et al [6] 2011 6817 United States 400 Toso et al [7] 2009 6478 United States 400 Zheng et al [8] 2008…”
Section: From Static To Dynamicmentioning
confidence: 99%
“…Therefore, serum AFP levels are useful for the early detection and differential diagnosis of HCC (18). For patients who undergo curative hepatectomy for localized HCC, AFP levels are also useful for the detection of recurrence, and are associated with prognosis (19)(20)(21). Based on the data of the present study, GTSF1 mRNA was expressed in 87.5% of AFP-positive samples, but only in 50% of AFP-negative samples.…”
Section: Discussionmentioning
confidence: 99%